The experiences of unemployed single mothers leading female headed households in Daveyton - Mbanjwa, Nompumelelo Precious (My University, 2018)
There are a growing number of female headed households in South Africa. Research shows that the majority of children among the black population in South Africa live in a household where only their mother is present. A large percentage of these single mothers are unemployed, have low levels of education and often tasked with the responsibility of caring and playing the provider role to their children. Since there is a high rate of single parenthood and unemployment among women in South Africa, research of this nature is crucial. This research study was aimed at discovering the experiences of unemployed single mothers leading female headed households. This research hopefully provided a fresh perspective as it was aimed at studying the experiences of young single mothers in the townships unlike the majority of the studies which often focused on older female heads located in the rural areas. The study sample included 15 participants comprising of single mothers leading female headed households who were residents of Daveyton and were between the ages of 20 to 33 years. This is a qualitative research study; research participants were selected using purposive and snowball sampling techniques. The data was collected using face - to - face in-depth interviews and the instrument used was a semi-structured interview schedule. The information gathered from the study was analyzed using thematic analysis. The findings in this study indicate that for most young women motherhood was unplanned and an unpleasant experience that gave rise to a number of issues. These included changes in the romantic relationships of the participants, feeling trapped in their current situation and power struggles in the household. Factors such as low levels of education resulted from motherhood and limited the livelihood choices of the mothers. Admittedly, participants used diverse livelihood strategies such as the child support grant, family members, and traditional healers, informal trading and stealing. The evidence in this study suggests that the support from family assisted in reducing the stress and challenges that came with motherhood.
A Report on a Research Study Presented to The Department of Social Work School of Human and Community Development Faculty of Humanities University of the Witwatersrand in Partial Fulfilment of the Requirements for the Degree Master of Arts in Social work, March 2018
Keywords: Single-parent families--South Africa; Single-parent families--Economic aspects--South Africa; Women heads of households--South Africa